Klippel-Feil Syndrome: Pathogenesis, Diagnosis, and Management. Issue 22 (15th November 2021) - Litrenta, Jody; Bi, Andrew S.; Dryer, Joseph W.
Abstract : Klippel-Feil syndrome (KFS), or congenital fusion of the cervical vertebrae, has been thought to be an extremely rare diagnosis. However, recent literature suggests an increased prevalence, with a high proportion of asymptomatic individuals. Occurring as a sporadic mutation or associated with several genes, the pathogenesis involves failure of cervical somite segmentation and differentiation during embryogenesis. Most commonly, the C2-C3 and C5-C6 levels are involved. KFS is associated with other orthopaedic conditions including Sprengel deformity, congenital scoliosis, and cervical spine abnormalities, as well as several visceral pathologies. There are several classification systems, some based on the anatomic levels of fusion and others on its genetic inheritance. Management of patients with KFS primarily involves observation for asymptomatic individuals. Surgical treatment may be for neurologic complaints, correction of deformity, concomitant spinal anomalies, or for associated conditions and varies significantly. Participation in sports is an important consideration. Recommendations for contact sports or activities depend on both the level and the number of vertebrae involved in the fusion. A multidisciplinary team should be involved in the treatment plan and recommendations for complex presentations.